Buccal Mucosal Graft Urethroplasty for Complex Urethral Strictures: A Single Center Study - Chalise, Pawan R; Luitel, Bhojraj; Chapagain, Suman; Poudyal, Sujeet; Pradhan, Manish M; Parajuli, Purushottam; Sharma, Uttam K; Gyawali, Prem R (Journal of Institute of Medicine Nepal, 2023)
Introduction: Urethral strictures have been a surgical challenge for the reconstruction urologists. Lichen Sclerosus (LS) is the most common cause of urethral stricture in the developing world. There are different free graft tissues for urethroplasty but buccal mucosal graft (BMG) urethroplasty is an effective and versatile procedure for inflammatory and long segment urethral strictures. Methods: A total of 64 cases who had complex urethral strictures underwent dorsal onlay BMG urethroplasty. BMG was harvested from cheeks or sublingual mucosa depending upon the length of the stricture. The catheter was removed after 3 weeks and patients were evaluated with uroflowmetry. The surgery was considered successful if subjective and objective parameters were satisfactory. Results: Average length of the harvested graft was 14.5 cm (10-18 cm) in 42 panurethral, eight distal penile, four proximal penile and bulbar, and 10 bulbar urethral strictures. Postoperative period was uneventful except in four, of which two developed urethral fistulas and the other two developed periurethral abscess which resolved after treatment. After catheter removal, all voided with satisfaction. All patients, reassessed after mean period of 21 months, had satisfactory voiding. Two patients underwent visual internal urethrotomy for stricture at proximal site of BMG placement. There were no complications observed in the donor site with complete healing in all. Conclusion: Dorsal onlay BMG Urethroplasty is an effective and versatile procedure for anterior urethral strictures with excellent results and with minimal donor site morbidity.